GAMBARAN PENGETAHUAN, SIKAP DAN PERILAKU MENGENAI HIV/AIDS PADA MAHASISWA PROGRAM STUDI PENDIDIKAN DOKTER UNIVERSITAS TANJUNGPURA - ., Desilianty Sari (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
AbstractBackground- West Kalimantan is becoming the sixth province that have high number of HIV/AIDS in Indonesia. Doctors graduated from Medicine and Health Science Faculty of Tanjungpura University will be primary care doctors that would diagnose HIV/AIDS cases so they need a good enough knowledge, attitude and behaviour of HIV/ AIDS.Objectives- To know the overview of knowledge, attitude and behaviour about HIV/AIDS among medical students of Tanjungpura University.Methodology? This research used cross-sectional study. Sample of this research were medical students of Tanjungpura University class of 2008, 2009 and 2010. Knowledge, attitude and behavior level about HIV/AIDS of 150 medical students were collected by completing questionnaire. The data was analyzed by SPSS 17.Result- There were 141 students (94%) had good level of knowledge, 130 students (86,7%) had good level of attitude and 120 students (80%) had good level of behavior. Class of year 2008 had a good level of knowledge 100%, good attitude 96% and good behavior 90%.Conclusion? Most of students have good knowledge (94%), good attitude(86,7%) and good behavior(80%). Class of 2008 have more higher knowledge, attitude and behavior than class of 2009 and 2010.Key words: knowledge attitude behavior HIV/AIDS medical students